Effect of drug interactions involving antiretroviral drugs on viral load in HIV population. Issue 4 (18th June 2015) - Iniesta-Navalón, Carles; Franco-Miguel, Juan José; Gascón-Cánovas, Juan José; Rentero-Redondo, Lorena
Abstract : Background: Most studies focus on potential drug interactions, without considering the effect of these on the response to antiretroviral (ARV) therapy. We assess the effect of potential drug–drug interactions (pDDIs) that could have lowered the ARV concentration (pDDI-lowerARV) on HIV viral load. Methods: Retrospective observational cohort study was conducted on all HIV-infected outpatients attending the Pharmacy Service of a regional reference hospital in Murcia (south-eastern Spain). The complete treatment was subsequently screened for pDDIs using the database 'InteraccionesHIV.com'. The study focused on interactions involving at least one ARV drug and, especially, any pDDI-lowerARV. Results: Two hundred and twenty-nine patients were included in the study. A total of 168 pDDIs were identified, of which 62 (36.9%) had the potential to lower ARV concentrations. In 77% of cases, the drug involved in the reduction of plasma concentrations was a protease inhibitor (PI), and in the rest of the drug interactions the ARV drug affected was a non-nucleoside reverse-transcriptase inhibitor. Baseline viral suppression was noted in 57.1% of patients with pDDI-lowerARV compared with 61.5% of patients without pDDI-lowerARV (p=0.605), and in 85.7% versus 79.7%, respectively, after a 24-week follow-up period (p=0.516). Conclusions: This study shows that prevalence of pDDI-lowerARV was high; however, no association was found between the presence of these interactions and virological failure. These results confirm the need for further studies to understand the consequences of interactions in real-life clinical practice, since most pharmacokinetic studies tend to evaluate the ability of interaction between two drugs under controlled conditions.